Effectiveness of Intradialytic Exercise and Foot Hand Massage On Physiological Response of Blood Pressure - Awan Hariyanto; Mimik Christiani (Poltekkes Kemenkes Semarang, 2021)
Background: End-stage acute and chronic kidney disease requires hemodialysis as an option for treating kidney failure. Hemodialysis patients are reported to experience depression and anxiety affecting blood pressure. Controlling blood pressure during hemodialysis is an important factor in supporting the success of hemodialysis treatment. Interventions that can be given to support anxiety management to have stable blood pressure in hemodialysis renal failure patients were intradialityc exercise and foot hand massage.Method : The research design used was pre-experimental in the form of one-group pre-post test design. The sampling technique used purposive sampling with a sample size of 20 respondents. Data analysis for data normality used shaphiro-whilk, for general data univariately used frequency distribution tables, while bivariate analysis in paired groups used the Wilcoxon statistical test with a significance level of ≤ 0.05.Result: The treatment of intradialityc exercise and foot hand massage had an effective effect on the physiological response to the anxiety in patients of renal failure with hemodialysis, including p value: systole blood pressure 0.003, diastole 0.015. Intradialytic exercise and foot hand massage given to patients of renal failure under hemodialysis treatment had an effective effect on the physiological response to the anxiety of systole and diastolic blood pressure.Conclusion : Intradialytic exercise and foot hand massage had an effective effect on stabilizing blood pressure and were recommended to be used as a non-pharmacological nursing